2020
DOI: 10.2166/wst.2020.254
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of eutrophication potential of municipal wastewater

Abstract: One of the main factors of the increased eutrophication level of surface waters is the high anthropogenic loads of biogenic substances discharged into water bodies. Municipal wastewaters, containing large amounts of nitrogen and phosphorus play one of the key roles in the acceleration of eutrophication intensity. The main direction in the prevention of eutrophication caused by wastewater discharge has become the reduction of nutrient loads introduced to wastewater receivers in accordance with strict legal requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Municipal wastewater discharge is a source of nitrogen loads in natural water bodies and is one of the main factors causing water eutrophication (Preisner et al 2020). With societal and economic development, water consumption and wastewater production has increased.…”
Section: Introductionmentioning
confidence: 99%
“…Municipal wastewater discharge is a source of nitrogen loads in natural water bodies and is one of the main factors causing water eutrophication (Preisner et al 2020). With societal and economic development, water consumption and wastewater production has increased.…”
Section: Introductionmentioning
confidence: 99%
“…The low nitrogen and phosphorus removal rates of AWT are considered to be its biggest drawbacks [ 17 ]. These biogenic substances are the main factors responsible for the rapid eutrophication and degradation of natural water bodies [ 18 ]. Fixation of nitrogen and phosphorus in digesters is driven solely by the growth of bacterial biomass, of which they are important building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen management is important for controlling urban non-point-source pollution (Preisner et al 2020). However, it has recently been found that PPs may control nitrogen concentrations in runoff to some degree (Abdollahian et al 2018), but NO 3 À -N is often leached from PPs (Bean et al 2007;Collins et al 2010).…”
Section: Introductionmentioning
confidence: 99%